Outcomes of a non-diffractive extended depth of focus intraocular lens in patients with well-controlled glaucoma and ocular hypertension - Jia-Ru Liu; Andrei-Alexandru Szigiato; Paul Harasymowycz (International Journal of Ophthalmology)
AIM: To assess visual outcomes and satisfaction of a non-diffractive extended depth of focus (EDOF) intraocular lens (IOL) in individuals with ocular hypertension (OHT) and well-controlled mild glaucoma undergoing cataract surgery. METHODS: An investigator-initiated, single-center, prospective, interventional, noncomparative study conducted in Montreal, Canada. The study enrolled 31 patients (55 eyes) with OHT or mild glaucoma who received a non-diffractive EDOF IOL (Acrysof IQ Vivity). Participants underwent sequential cataract surgery with the Vivity IOL. Follow-up evaluations occurred at 1d, 1, and 3mo postoperatively, assessing uncorrected distance, intermediate, and near visual acuity. Questionnaires (QUVID: Questionnaire for visual disturbances and IOLSAT: Intraocular lens satisfaction) were administered pre and post-operatively to measure visual disturbances and spectacle independence in various lighting. Safety parameters included intraocular pressure (IOP), glaucoma medications, spherical equivalence, mean deviation and pattern standard deviation or square root of lost variance on Octopus visual field. RESULTS: At 1 and 3mo postoperatively, significant improvements were observed in uncorrected distance and intermediate visual acuity. Spectacle independence was enhanced for distance and intermediate vision, especially in bright light settings. Spectacle-free intermediate vision was improved even in dim lighting. Visual disturbances, particularly glare symptoms, were reduced, and there was a notable decrease in IOP and glaucoma medication burden at 3mo. There was more hazy vision postoperatively with no impact on visual acuity and visual satisfaction. CONCLUSION: The non-diffractive EDOF lens improves distance and intermediate spectacle-free visual function in patients with OHT and well-controlled glaucoma. The findings highlight significant improvements in visual acuity, reduced glare, enhanced spectacle independence, and improved visual performance in different lighting conditions.